2021
DOI: 10.18632/aging.202784
|View full text |Cite
|
Sign up to set email alerts
|

The critical role of peroxiredoxin-2 in colon cancer stem cells

Abstract: Colon cancer stem cells (CCSCs) play an important role in facilitating colon cancer occurrence, metastasis and drug resistance. The results of our previous studies confirmed that the well-studied antioxidant gene peroxiredoxin-2 (PRDX2) promotes colon cancer progression. However, the underlying function and mechanisms associated with PRDX2 remodeling in the context of CCSCs have remained poorly studied. In our present study, we demonstrated that PRDX2 is highly expressed in CD133/CD44-positive colon cancer tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 57 publications
1
10
0
1
Order By: Relevance
“…Previous studies demonstrated that CSC of OSCC show resistance to cisplatin through reduced oxidative stress, 18 and stem cells from pancreatic cancer exhibit high levels of PRDX2 19 . Also, PRDX2 knockdown inhibits tumor cell dedifferentiation in colorectal cancer, suggesting its importance to stemness maintenance 20 …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies demonstrated that CSC of OSCC show resistance to cisplatin through reduced oxidative stress, 18 and stem cells from pancreatic cancer exhibit high levels of PRDX2 19 . Also, PRDX2 knockdown inhibits tumor cell dedifferentiation in colorectal cancer, suggesting its importance to stemness maintenance 20 …”
Section: Discussionmentioning
confidence: 97%
“…19 Also, PRDX2 knockdown inhibits tumor cell dedifferentiation in colorectal cancer, suggesting its importance to stemness maintenance. 20 It is well reported that CSC can repair DNA damage. 21 By assessing the accumulation of phospho-H2A.X, we identified that the CSC present lower DNA damage than the non-stem cells subpopulation derived from cisplatin-resistant OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…The authors conclude that the CD133/NRF2 axis contributes to the development of a CSC-like phenotype [ 105 ]. High expression of the antioxidant gene peroxiredoxin-2 ( PRDX2 ) has been attributed to CD133 + CD44 + cells and is associated with colon cancer CSC stemness [ 106 ]. Depletion of PRDX2 substantially suppressed maintenance of stemness, together with migration, invasion, and metastasis.…”
Section: Redox-signaling In Cscs: Role Of Nrf2mentioning
confidence: 99%
“…Depletion of PRDX2 substantially suppressed maintenance of stemness, together with migration, invasion, and metastasis. Notably, knockdown of PRDX2 increased ROS-levels in CD133 + CD44 + , making CSCs sensitive to oxidative stress and chemotherapy [ 106 ].…”
Section: Redox-signaling In Cscs: Role Of Nrf2mentioning
confidence: 99%
“…O estresse oxidativo promovido pelo acúmulo de espécies reativas de oxigênio (EROS) é um dos mecanismos de resposta ao câncer, que por sua vez ocasiona danos na molécula de DNA das células (LEE et al, 2020) KAMEMURA et al, 2012;PARMIGIANI et al, 2008b;RYU et al, 2017;TANG et al, 2018) PENG et al, 2021;WANG et al, 2016).…”
Section: Discussionunclassified